1992
DOI: 10.1093/nar/20.4.825
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid induction of CRE-binding protein isoform mRNAs in rat C6 glioma cells

Abstract: Mammalian cells express several distinct isoforms of transcription factor CREB (cAMP-responsive element binding protein). At least two forms, alpha- and delta CREB, arise through alternative splicing of the CREB gene transcript. In this communication we demonstrate that the mRNAs of several CREB isoforms are expressed in rat C6 glioma cells and that the intracellular levels of these mRNAs are markedly induced by the synthetic glucocorticoid dexamethasone. Nuclear run-off assays show that the induction occurs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Thus, direct interactions between the cAMP-dependent pathway and steroid receptor activation may be operative in modulating gene expression. In addition, the synthesis of the cAMP-responsive element binding protein that mediates the cAMP-induced changes in gene transcription is markedly increased by dexamethasone ( 18). Our data, however, do not distinguish between these possibilities leaving presently unanswered the question of whether the dexamethasone-cAMP combination affects insulin gene transcription through a transcriptional, a posttranscriptional, or both mechanisms.…”
Section: Methodscontrasting
confidence: 63%
See 1 more Smart Citation
“…Thus, direct interactions between the cAMP-dependent pathway and steroid receptor activation may be operative in modulating gene expression. In addition, the synthesis of the cAMP-responsive element binding protein that mediates the cAMP-induced changes in gene transcription is markedly increased by dexamethasone ( 18). Our data, however, do not distinguish between these possibilities leaving presently unanswered the question of whether the dexamethasone-cAMP combination affects insulin gene transcription through a transcriptional, a posttranscriptional, or both mechanisms.…”
Section: Methodscontrasting
confidence: 63%
“…However, it is unlikely that such a lack ofinhibitory effect alone could account for the 40% increase in the steady state levels of insulin mRNA we oW served. Rather, it is most likely that this net increase reflects also the involvement of other positive factors, such as the increased synthesis of the cAMP-responsive element binding protein ( 18). Because the regulation of the insulin gene is defective in dispersed islet cells, these factors should be somehow dependent on the maintenance ofthe contacts : cells normally establish within the islets ofLangerhans.…”
Section: Methodsmentioning
confidence: 99%
“…Jungmann et al . [38] showed that glucocorticoids induce the CREB isoform mRNA in rat C6 glioma cells, but counteract the induction of lactate dehydrogenase by cAMP. Many different transcription factors can also bind to CRE.…”
Section: Discussionmentioning
confidence: 99%
“…The cytosolic and particulate fractions were also assayed for the presence of CRE-binding proteins. CREB is constitutively expressed in C6 (Jungmann et al, 1992), and its level rapidly decreased in both fractions on stimulation with dbcAMP ( Fig. 6B).…”
Section: Cellular Distribution and Activity Of Pkamentioning
confidence: 94%